Transmisi, Sanad Keilmuan, dan Resepsi Hadis Puasa Dala’il al-Khayrat - Rafi’i , Melati Ismaila; Qudsy, Saifuddin Zuhri (Mutawatir : Jurnal Keilmuan Tafsir Hadith, 2020)
Dala’il al-khayrat is a kind of fasting that has been practiced by santris, mostly, in Central and East Java. It requires the persons to fasting in range of one or three years continually. This paper departs from questions on how is this practice carried out, how does the transmission of knowledge come from and how does the foundation of the sacred text (such as hadith) lie behind the practice. By using historical method, the authors conclude that the practice of dala’il cannot be separated from the role of Shaykh Yasin who taught his students through the process of ijazah. In addition, we found that the transmission of knowledge on dala’il al-khayrat rooted from Shaykh Mahfud al-Turmusi, an Indonesian prominent scholar who taught at haramayn in the 20th Century.